OSTEOPOROSIS KNOWLEDGE, ATTITUDES, AND PRACTICES AMONG STUDENTS - Subrata, Mariany Puspita; Girsang, Ermi; Manalu, Putranto (Kesmas Indonesia, 2025)
Prevention of osteoporosis at a young age is very necessary. Evidence suggests that modifying some lifestyle habits can help reduce the incidence of osteoporosis. However, limited research has been conducted to assess knowledge, attitudes, and lifestyles related to osteoporosis among young people. Good knowledge and attitude towards osteoporosis will result in real osteoporosis prevention actions. Therefore, this study aims to evaluate knowledge, attitudes and practices about osteoporosis in a group of students.This study was conducted using an analytical observational method using a cross-sectional design. The subjects of this study were 384 students of Universitas Prima Indonesia. Data were analyzed in univariate and bivariate forms. Bivariate analysis was used to see the difference in total scores of knowledge, attitudes and practices based on gender and field of science using the t-independent test and the Mann Whitney test. In analyzing the influence of knowledge and attitudes on the formation of practices, the Pearson product moment test was used. The results showed that the average knowledge (34.61 ± 4.77) and attitudes (28.57 ± 6.56) of students regarding osteoporosis were classified as moderate, student practices regarding osteoporosis were classified as poor (4.58 ± 2.24). The results of the bivariate test showed that there was a difference in the average total score of knowledge about osteoporosis between men and women (p = 0.021), health and non-health fields (p = 0.003). Furthermore, there was a correlation between attitudes and practices regarding osteoporosis (r: 0.144; p = 0.005). This study shows the need for the implementation of educational and awareness programs for students about risk factors and prevention of osteoporosis which must be designed based on the parameters of the health belief model.